2013
DOI: 10.1016/j.devcel.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Interactions Eliminate Unfit Embryonic Stem Cells at the Onset of Differentiation

Abstract: SummaryA fundamental question in developmental biology is whether there are mechanisms to detect stem cells with mutations that, although not adversely affecting viability, would compromise their ability to contribute to further development. Here, we show that cell competition is a mechanism regulating the fitness of embryonic stem cells (ESCs). We find that ESCs displaying defective bone morphogenetic protein signaling or defective autophagy or that are tetraploid are eliminated at the onset of differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
302
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(323 citation statements)
references
References 33 publications
19
302
1
1
Order By: Relevance
“…While the identity of the engulfing cells and whether engulfment itself mediates competition in Drosophila are controversial, we clearly show that neighboring cell-mediated engulfment and killing occur in mixed populations of human cells. Other mechanisms of competition between mammalian cells have been demonstrated, including the differential extrusion of cells of mixed genotypes from monolayer cultures [9,10], competition between cells of the early embryo [36][37][38], and competition between hematopoietic progenitors driven by differences in p53 activity [39,40]. Perhaps diverse competition mechanisms reflect a stringent requirement for homeostasis in different contexts within various tissue types of metazoan organisms during development and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…While the identity of the engulfing cells and whether engulfment itself mediates competition in Drosophila are controversial, we clearly show that neighboring cell-mediated engulfment and killing occur in mixed populations of human cells. Other mechanisms of competition between mammalian cells have been demonstrated, including the differential extrusion of cells of mixed genotypes from monolayer cultures [9,10], competition between cells of the early embryo [36][37][38], and competition between hematopoietic progenitors driven by differences in p53 activity [39,40]. Perhaps diverse competition mechanisms reflect a stringent requirement for homeostasis in different contexts within various tissue types of metazoan organisms during development and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two studies (Claveria et al, 2013, Sancho et al, 2013 have shown that cell competition has a functional role during early mouse development. At the epiblast stage there is endogenous cell competition so that cells with lower levels of Myc are eliminated (Claveria et al, 2013).…”
Section: Cell Competition In Vertebratesmentioning
confidence: 99%
“…It is noteworthy that this low apoptotic threshold might play an equally important role in other types of stresses, such as those associated with a lack of nutrients or growth factors, or Myc-driven cell competition (Clavería et al, 2013;Sancho et al, 2013). Thus, because of the high level of vigilance of Epi cells at the E5.5-6.5 transition, it is not surprising that so many mouse mutants are lethal at this specific stage, a representative example being Mdm2 −/− (Jones et al, 1995): the depletion of this p53 inhibitor induces apoptosis after E5.5 in Epi cells, which we now show concomitantly express consistent levels of p53 and are very close to crossing the apoptotic threshold.…”
Section: Elevated Expression Of Noxa Bim and Bak Lowers The Apoptotimentioning
confidence: 99%